Cognitive Aids for Role Definition (CARD) to improve interprofessional team crisis resource management: An exploratory study. Issue 5 (2nd September 2016) - Renna, Tania Di; Crooks, Simone; Pigford, Ashlee-Ann; Clarkin, Chantalle; Fraser, Amy B.; Bunting, Alexandra C.; Bould, M. Dylan; Boet, Sylvain
ABSTRACT: This study aimed to assess the perceived value of the Cognitive Aids for Role Definition (CARD) protocol for simulated intraoperative cardiac arrests. Sixteen interprofessional operating room teams completed three consecutive simulated intraoperative cardiac arrest scenarios: current standard, no CARD; CARD, no CARD teaching; and CARD, didactic teaching. Each team participated in a focus group interview immediately following the third scenario; data were transcribed verbatim and qualitatively analysed. After 6 months, participants formed eight new teams randomised to two groups (CARD or no CARD) and completed a retention intraoperative cardiac arrest simulation scenario. All simulation sessions were video recorded and expert raters assessed team performance. Qualitative analysis of the 16 focus group interviews revealed 3 thematic dimensions: role definition in crisis management; logistical issues; and the "real life" applicability of CARD. Members of the interprofessional team perceived CARD very positively. Exploratory quantitative analysis found no significant differences in team performance with or without CARD ( p  > 0.05). In conclusion, qualitative data suggest that the CARD protocol clarifies roles and team coordination during interprofessional crisis management and has the potential to improve the team performance. The concept of a self-organising team with defined roles is promising for patient safety.